In-situ TiC particle-reinforced Hastelloy X superalloy fabricated by laser additive manufacturing - Chen Wang; Li Yang; Rui-Xin Sheng; Shuai Guan; Zhong-Nan Bi; Hua Zhang; Hai-Liang Huang; Liang Jiang; Li-Long Zhu; Xin Zhou (Journal of Materials Research and Technology)
In-situ metal matrix composites are desirable for achieving optimum mechanical properties. This study investigated the enhancement of mechanical performance in Hastelloy X (HX) superalloy through in-situ synthesis of TiC and γ′ phases via titanium (Ti) addition using a high-throughput laser additive manufacturing system. The influence of Ti content on phase evolution, microstructure, and mechanical properties was comprehensively analyzed for both the as-deposited and heat-treated HX superalloys. The results revealed that increasing Ti content exacerbated micro-segregation during the deposition, promoting pronounced dendritic growth and a higher σ phase volume fraction. These microstructural changes enhanced tensile strength while concurrently elevated cracking susceptibility, with macroscopic cracking detected upon reaching 5 wt% Ti. Following heat treatment, micro-segregation was significantly reduced. In alloys containing 2–4 wt% Ti, TiC and nano-sized γ′ phases precipitated after heat treatment, leading to a 40 % improvement in yield strength and tensile strength compared to the baseline HX superalloy, while maintaining an elongation of approximately 30 %.